Cross-modal generalization of receptive and expressive vocabulary in children with autism spectrum disorder. (January 2019) - Su, Pumpki L; Castle, George; Camarata, Stephen
Background and aims: Word learning is an area that poses a particular challenge to children with autism spectrum disorder. A unique challenge for this population is generalization of learned skills across new learning contexts. In clinical settings, a common assumption in teaching vocabulary for children with autism spectrum disorder is that learning in one modality will generalize incidentally to untreated modalities, but very few studies have evaluated the validity of this assumption. The purpose of this study was to investigate receptive and expressive word acquisition and cross-modal generalization in children with autism spectrum disorder. Methods: A single-case parallel treatments design was used to compare word learning and cross-modal generalization in children with autism spectrum disorder. Ten children with autism spectrum disorder were taught unfamiliar vocabulary words in a combined storybook and play intervention. For each child, half of the target words were trained expressively and the other half were trained receptively by random assignment. No direct cross-modal instruction was delivered. A series of probe sessions were completed to assess participants' within-modal learning and cross-modal generalization of vocabulary learning. Results: All children learned target words in both receptive and expressive conditions, as evidenced by an average of 80% accuracy across three trials at the end of each intervention. Overall, cross-modal generalization was higher for the expressive-to-receptive direction than for the receptive-to expressive direction. Nine out of ten children demonstrated successful cross-modal generalization on the expressive-to-receptive probes and only three children demonstrated successful cross-modal generalization on the receptive-to-expressive probes. Large variability was observed with regard to number of intervention sessions needed to reach mastery criterion and there were individual patterns of word learning. Conclusion: Contrary to the assumption that vocabulary learning will be "automatically" generalized across modalities, results from this study indicate that cross-modal generalization at the word level is not automatic nor consistent in children with autism spectrum disorder, particularly in the receptive-to-expressive direction. Implications: The finding that more children demonstrated expressive-to-receptive generalization than the opposite direction suggests that targeting expressive vocabulary first with the goal of incidentally increasing receptive vocabulary may be more efficient than starting with the receptive modality. Additionally, the finding that not all children demonstrated successful expressive-to-receptive cross-modal generalization indicates that teaching vocabulary in the expressive modality exclusively does not guarantee receptive understanding in this population. We recommend that practitioners periodically monitor children's vocabulary learning in both modalities or set an explicit generalization goal to ensure complete learning of trained words.